Genetic instability in Drosophila melanogaster: P-element mutagenesis by gene conversion. - Geyer, P.K.; Richardson, K.L.; Corces, V.G.; Green, M.M. (Proceedings of the National Academy of Sciences of the United States of America, 1988)
We report the molecular characterization of several P element-induced mutations and their revertants at the yellow (y) locus of Drosophila melanogaster. One of the mutants analyzed, y76d28, results from the insertion of a P element into the 5'-transcribed, untranslated portion of the y gene. Sequence analysis of several revertants of y76d28 shows that P excision occurs imprecisely. These events result in insertion of additional ATG codons in the y locus mRNA but are without phenotypic effect. In addition, we describe the molecular structure of P-associated mutations induced in a near wild-type revertant of y76d28 that carries an internally deleted 0.4-kilobase P element in the 5' noncoding region. Sequence analysis of two of these mutants demonstrates that they arose as a result of the integration of a larger P element at the exact location as in the parental stock without the 8-base-pair additional duplication associated with P insertions. The phenotype of these y alleles is dependent on the size and orientation of the integrated P element. We infer that P-element replacement in these mutants has occurred by a recombination/gene conversion mechanism.